Hypertension in children with intellectual disabilities: a population not to be overseen - Wyszyńska, Justyna; Łuszczki, Edyta; Seeman, Tomas; Simonetti, Giacomo D; Nyankovska, Olena; Wójcik, Małgorzata; Kozioł-Kozakowska, Agnieszka; Peletidi, Aliki; Mazur, Artur; Alvarez-Pitti, Julio; Lurbe, Empar (Journal of hypertension, 2025)
Hypertension (HTN) is a significant public health concern affecting individuals across all age groups, including those with and without disabilities. Among children and adolescents, particularly those with intellectual disabilities, the risk of HTN is heightened due to factors such as obesity, low physical activity, and comorbid conditions. Regular blood pressure (BP) monitoring is essential, considering the challenges in measurement accuracy among children with intellectual disabilities. Beyond traditional lifestyle modifications, individualized dietary interventions and structured physical activity programs play a fundamental role in HTN prevention and management. Additionally, optimizing sleep quality and addressing comorbidities are essential for improving long-term health outcomes. The updated recommendations emphasize a broader specialist involvement, including endocrinologists, nephrologists, cardiologists, and rehabilitation specialists, to ensure comprehensive care. The integration of these approaches, along with appropriate pharmacological strategies whenever necessary, is crucial for achieving health benefit. This article provides practical guidance for primary care providers, specialists, and caregivers, advocating for a collaborative, patient-centered approach to reducing cardiovascular risks and enhancing the quality of life for children with intellectual disabilities.
Keywords: Child; intellectual disability; Intellectual Disability; Exercise; Humans; Adolescent; recommendations; sleep; lidé; cvičení; hypertension; hypertenze; obesity; Hypertension; dítě; physical activity; mentální retardace; mladiství